San-Antonio Ltd. : competition and domination in the field of crime literature and film noir in post 1950s France - Jeannerod, Dominique François (Trinity College (Dublin, Ireland). Department of French, 2007)
The modernity of the detective novel, associated with its narratological and formal innovations, entails a reversal of the relationship between the text and its author. The situation of the detective fiction writer, with his submission to the laws of genre, to the conditions of exploitation it implies and to his actual relegation in favour of his characters succeeds in a 'functionalisation' of the author, as seen in Post-Structural criticism. The response to this dissolution of authority results in two distinct strategies among French Post-War detective fiction authors. On the one hand, the writer emphasizes the commercial aspect of his work and his situation as producer within the cultural industry. On the other hand, he instigates a questioning of literary hierarchies and the symbolic discrimination they imply, leading to his affirmation of the inherently literary quality of his production.
Keywords: French, Ph.D.; Ph.D. Trinity College Dublin